Upaya Peningkatan Cakupan Deteksi Dini Kanker Serviks dengan KarS-A (Kartu Skor Aim) pada WUS Ranting ‘Aisyiyah Socah Bangkalan - A’im Matun Nadhiroh; Annisa Wigati Rozifa; Fulatul Anifah; Awwalul Wiladatil Qodliyah (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service aims to increase WUS knowledge and attitudes about cervical cancer and increase WUS motivation to carry out early detection of cervical cancer. Methods of solving problems with socialization about cervical cancer and early detection of cervical cancer in a programmed manner; health education through counseling about cervical cancer and early detection of cervical cancer; and giving KarS-A and how to use it. This community service includes an initial survey, preparation, and implementation (socialization and counseling about cervical cancer and the importance of early detection of cervical cancer, socialization about KarS-A and how to use it, as well as early detection of cervical cancer with VIA examination), and evaluation of activities. The results of this community service activity were obtained by increasing women of childbearing age's knowledge and attitudes about cervical cancer and increasing women of childbearing age motivation as indicated by early detection of IVA cervical cancer.